Disturbance maintains native and exotic plant species richness in invaded grassy woodlands. (19th February 2017) - Driscoll, Don A.
Abstract: Question: Community invasion and dominance by exotic species can be abetted by disturbance and elevated nutrient levels. However, impacts of exotics on native species are often manifest through competition, suggesting disturbance or nutrient management could benefit native species. I therefore asked: does nutrient reduction through carbon addition, or disturbance to reduce biomass, contribute to restoration by increasing occurrence and richness of native plant species? Location: SE Australia. Methods: Using a field experiment spanning 4 yrs, this study assessed the potential for carbon addition, three types of disturbance (burn, crop, slash) and their interaction with native herbivore grazing to reduce exotic, and increase native, plant species in a critically endangered grassy woodland in SE Australia. Results: Adding carbon reduced occurrence of one native and three exotic species, while increasing one exotic and one native species. The value of adding carbon for restoration was therefore ambiguous. Fencing to exclude the high‐density kangaroo population had temporary beneficial effects, suggesting that grazing reduced the number of native and exotic plant species by up to 56% and 21%, respectively. Species richness declined by year 3 in fenced areas, likely through competitive exclusion. Burn, slash and crop treatments also provided disturbance that maintained species richness and occurrence of many species, both native and exotic. Most grazing interactions reflected the benefit of alternative disturbance in the absence of grazing. However, there was also evidence that two species declined when crop and grazing acted in combination. Conclusions: Very high grazing by native herbivores reduced plant species richness in this study. However, grazing or other forms of disturbance appeared critical for preventing a small number of exotic species from driving down occurrence and richness of many other native and exotic plant species. Although increased exotic species richness is undesirable, disturbance led to a better outcome for conservation than the low‐disturbance alternatives. Abstract : The value of adding carbon for restoration was ambiguous because it caused increases and decreases in native and exotic plant species. Native herbivore grazing reduced species richness. However, richness was more severely reduced without disturbance because plots became dominated by a few exotic species. Although disturbance increased exotic richness, concomitant increases in native richness meant disturbance achieved better conservation outcomes.